Faktor-Faktor yang Berhubungan dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Oesapa - Atri Yanti Enga Likka; Utma Aspatria; Sarci Magdalena Toy (Yayasan Literasi Sains Indonesia, 2025)
Stunting is a nutritional problem that is still a global problem. Stunting is a condition of growth failure caused by lack of nutrition in the first 1000 days of life. The growth and development process of toddlers certainly requires adequate and appropriate nutrition so that health problems do not occur. Poor nutritional quality in toddlers will cause stunting. Stunting in toddlers is caused by two factors, namely direct and indirect factors. Direct factors such as food consumption patterns and history of infectious diseases, while indirect factors include the level of parental knowledge and parental income. This study was conducted to analyze the factors related to the incidence of stunting in the Oesapa Health Center work area. The type of research conducted is an observational analytical study with a case-control design. The population of this study were mothers who had toddlers aged 6-59 months with a sample of 80 people. The data collected were analyzed using the Chi-Squere test. The results of the bivariate analysis showed that the knowledge variable (p-value = 0.143) had no relationship with food consumption patterns, parental income (p-value = <0.005) was related to consumption patterns, while food consumption patterns (p-value = <0.005), and history of infectious diseases (p-value = <0.005) were related to the incidence of stunting in toddlers in the Oesapa Health Center work area.